Formulation and evaluation of nanoemulsions from Jasminum officinale essential oil for controlling postharvest browning and maintaining quality in jasmine (Jasminum sambac) flowers - Yeamsuriyotai, Kittiya; Pradabkun, Natthamon; Manichart, Nutcha; Yonsawad, Nipaporn; Khamchatra, Na-monrug; Laosinwattana, Chamroon; Teerarak, Montinee; Somala, Naphat (Frontiers in Plant Science, 2025)
The jasmine (Jasminum sambac (L.) Aiton) flower has delicate petals, resulting in rapid browning after harvest. The aim of this study was to search for an innovative postharvest treatment for delaying browning of jasmine petals using plant essential oils. J. officinale L. f. var. grandiflorum (L.) essential oil was found to reduce peroxidase activity in jasmine flower by 44.21% in the in vitro condition. The antioxidant activities and chemical composition of J. officinale essential oil were subsequently characterized. The essential oil exhibited the ability to scavenge 2,2-diphenyl-1-picrylhydrazil (DPPH) radicals with a 50% inhibition (EC50) value of 6.72 ± 0.89 mg/mL, a chelating effect with EC50 value of 7.42 ± 1.59 mg/mL, and reducing power with EC0.5 value of 14.89 ± 0.73 mg/mL. GC-MS analysis detected 29 compounds in the oil, with benzyl alcohol (20.68%) and benzyl acetate (19.87%) predominating. As plant essential oils have restricted water solubility, an oil-in-water emulsion was formulated using a spontaneous emulsification method. The resulting J. officinale essential oil naonoemulsion (JEN) had an oil droplet size of 70.2 ± 0.39 nm and a narrow polydispersity index. In vivo testing confirmed the inhibitory effects of JEN on jasmine flower browning and relevant enzyme activities. Jasmine flowers were soaked in various concentrations of JEN for 5 min, packed in polyethylene plastic bags, and stored in a refrigerator at 10 ± 3°C with relative humidity 66 ± 5%. Flowers treated with 1 and 2 mg/mL JEN showed effective delay of petal browning and maintained good quality with minimum flower opening index, high freshness score, and high color retention index. JEN treatment also reduced phenylalanine ammonia lyase (PAL), polyphenol oxidase (PPO), and peroxidase (POD) activities, indicating postponement of the browning process. In addition, scanning electron microscopy micrographs of treated flower epidermis cells revealed delayed cell wall collapse, indicating retention of intact cells. Taken together, these results support JEN as a potential preventative of enzymatic browning and hence petal browning in jasmine flower.